E-learning Platform to Teach Reading for High School Students: Computer-Assisted Language ‎Learning (CALL)‎ - Nugraheni, Susari; Fasikh, Mukhlasul (IAIN KENDARI, 2025)
In Indonesia, even though it has not yet widely used, computer starts to be an alternative tool in ‎teaching activity. By using technology, it is hoped could create more effective pedagogical ‎environment. Therefore, this study examined the use of e-learning platform, namely Blendspace, ‎Socrative, and Padlet in teaching Reading for L2 in Budi Mulia Dua Senior High School. These three ‎platforms are friendly users’ application available online. The aim of the research was to explore ‎the scope of these platforms in facilitating students learning English. Thus, mixed method was used ‎as research methodology. It is used action research as qualitative approach and experimental ‎research as quantitative approach. The findings show that the platforms enhance students’ ‎motivation and curiosity of learning English. It is counted by using Socrative there were 72.0% of ‎students in Advance Class get the good score, while for Low Level Class, it was only 46.2%. At the ‎same time, Blendspace creates effective learning process. Blended learning happens in this activity ‎because students could independently look back the lesson outside of the class. Salient way arises ‎as the implication of teacher materials on Blendspace. Another salient concept and dynamic ‎communication was occurred in Padlet. The results also point out that, even though there are some ‎drawbacks such as bad Wi-Fi connection and distraction to open others website, the benefit of the ‎platforms in the form of direct evaluation and live interaction create an enjoyable atmosphere at ‎class.‎